Asas Publisitas dalam Hukum Jaminan; Telaah Kritis Terhadap Perspektifitas Perlindungan Kreditur - Nur Lailah; Nafisatus Saidah; Yoeand Nadziifah Shafwah; Muhammad Nazzamuzzaman; Ahmad Musadad (IAIN Langsa, 2025)
Ideally, the publicity principle in security law functions as a transparency instrument to provide legal certainty and maximum protection for creditors over secured objects. However, in practice, this principle often faces distortions, particularly in fiduciary guarantees that are not registered, leading to legal uncertainty and weakening the creditor’s position in the event of a dispute. This study aims to critically examine the effectiveness of the publicity principle in protecting creditors’ interests within Indonesia’s security law framework. The research method employed is a literature study with a qualitative-descriptive approach, relying on primary sources such as legislation and secondary sources including legal literature. The findings indicate that the implementation of the publicity principle has not been fully effective in ensuring legal certainty for creditors, primarily due to weak enforcement of registration obligations and the absence of strict sanctions for violations. Therefore, a reformulation of the legal protection mechanism is necessary to better respond to creditors' interests.